Pengaruh Dispersi Hidraulik Aliran pada Bangunan Pengambilan Irigasi Untuk Efisiensi Debit: The Effect of Flow Hydraulic Dispersion on Irrigation Setting Structure for Discharge Efficiency - Isnaeni, Muhammad; Alma'Ruf, Mochammad Dian; Majdi, Abdul Ghoni; Eddy Suwandi; Waskito, Tri Nugroho (Himpunan Ahli Teknik Hidraulik Indonesia (HATHI), 2025)
Fluid flow separation occurs when the fluid flow encounters an obstacle or changes direction, causing the fluid particles to slow down or change direction. This change in velocity can cause fluid particles to move away from the boundary layer, leading to vortices forming. This type of flow separation can occur when the fluid encounters an area of ​​adverse pressure gradient, which can cause the fluid to slow down and flow in the opposite direction. In this research. A case study of one of the irrigation intake structures with curved horizontal alignments with imperfect radians. Trace anomalies in longitudinal sections that require a dispersivity specification that combines the effects of vertical shear dispersion and horizontal turbulent diffusion. This research aims to determine the effect of turbulence dispersion and diffusion on offtake structures with anomalous flow parameters and curved horizontal alignments that carry aquatic trees and debris. The research methods begin 1) Mapping canal and structure alignments using HEC-RAS numerical modelling, 2) Analysis using the Vertically Averaged and Moment (VAM) equation to describe the distribution of hydrostatic forces in cross sections to determine vertical dispersion and 3) Analysis of Reynolds number (Re) which influences turbulence in the flow so that waste does not pass downstream of the canal and has the potential to enter the secondary canal. This research provides recommendations for the efficiency of flow discharge in the canal that crosses the intake structures without reducing supply for irrigation but without creating flow turbulence that is detrimental to discharge drainage operations.